Laser‐induced melting experiments: Simulation of short‐term high‐temperature impact processes. (30th January 2017) - Ebert, M.; Hecht, L.; Hamann, C.; Luther, R.
Abstract: This study introduces an experimental approach using direct laser irradiation to simulate the virtually instantaneous melting of target rocks during meteorite impacts. We aim at investigating the melting and mixing processes of projectile (iron meteorite; steel) and target material (sandstone) under idealized conditions. The laser experiments (LE) were able to produce features very similar to those of impactites from meteorite craters and cratering experiments, i.e., formation of lechatelierite, partial to complete melting of sandstone, and injection of projectile droplets into target melts. The target and projectile melts have experienced significant chemical modifications during interaction of these coexisting melts. Emulsion textures, observed within projectile‐contaminated target melts, indicate phase separation of silicate melts with different chemical compositions during quenching. Reaction times of 0.6 to 1.4 s could be derived for element partitioning and phase‐separation processes by measuring time‐depended temperature profiles with a bolometric detector. Our LE allow (i) separate melting at high temperatures to constrain primary melt heterogeneities before mixing of projectile and target, (ii) quantification of element partitioning processes between coexisting projectile and target melts, (iii) determination of cooling rates, and (iv) estimation of reaction times. Moreover, we used a thermodynamic approach to calculate the entropy gain during laser melting. The entropy changes for laser‐melting of sandstone and iron meteorite correspond to shock pressures and particle velocities produced during the impact of an iron projectile striking a quartz target at a minimum impact velocity of ~6 km s −1, inducing peak shock pressures of ~100 GPa in the target.